A Case Report of Sporadic Adult Neuronal Intranuclear Inclusion Disease (NIID) With Stroke-Like Onset - Lin, Pan; Jin, Hang; Yi, Kun-Chang; He, Xiang-Sheng; Lin, Shi-Fang; Wu, Gang; Zhang, Zai-Qiang (Frontiers in Neurology, 2020)
Background: Neuronal intranuclear inclusion disease (NIID) is a rare neurodegenerative disease. The clinical manifestations of NIID are complex and easily misdiagnosed. Based on the current knowledge of this disease, it is usually chronic, with almost no acute cases. Stroke-like disease is an extremely rare type of NIID. Case Presentation: A 61-year-old woman was admitted to our hospital with sudden left limb weakness. Diffusion magnetic resonance imaging (MRI) demonstrated high signal intensity in the skin-medullary junction area. Tissue pathology showed eosinophilic inclusions in the nuclei of the sweat gland cells and fat cells of the skin. Subsequent genetic analysis of the fragile X chromosome mental retardation gene 1 (FMR1) gene showed that the CGG repeat number was in the normal range, excluding fragile X-related tremor/ataxia syndrome (FXTAS). After three weeks of hospitalization, the patient's condition improved, and the left limb muscle strength recovered. Her symptoms were almost completely diminished after three months. Conclusion: This case demonstrates the strong clinical heterogeneity of NIID. NIID can manifest as acute hemiplegia and a stroke-like attack. This case study provides new information for the diagnosis of NIID and the classification of the clinical characteristics.